2019
DOI: 10.21608/ejchem.2019.13001.1813
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Polypropylene Loaded by Cubic Cuprous Oxide Micro Particles

Abstract: R ECENTLY, nanotechnology of metals and their oxides is increased and became important for production of antimicrobial textiles. In situ synthesis of micro cuprous oxide particles (Cu 2 O), 1-30 mM/L onto non-woven polypropylene and study the antimicrobial activity were investigated. Cu 2 O micro particles were prepared by chemical method using copper sulphate pentahydrate, sodium hydroxide and glucose as a reducing agent at 90 o C for 2 hrs, followed by pad-dry-cure at 150ºC for 5min. C u 2 O content onto PP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…As the heating proceeds from an external source, the surface is first melted, then particles could be attached to it without significant changes in NWF crystal morphology. [ 19 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the heating proceeds from an external source, the surface is first melted, then particles could be attached to it without significant changes in NWF crystal morphology. [ 19 ]…”
Section: Resultsmentioning
confidence: 99%
“…As the heating proceeds from an external source, the surface is first melted, then particles could be attached to it without significant changes in NWF crystal morphology. [19] Micrographs of modified NWF using Methodologies A and B, as well as, particles and neat NWF are presented in Figure 2. A wide particle distribution of minerals is evident from Figure 2A; meanwhile, at high magnification, zeolite-rich sectors can be distinguished over volcanic glass (Figure 2B).…”
Section: Materials Characterizationmentioning
confidence: 99%
“…The particle size of CuO NPs was obtained by TEM analysis figure (10), the distribution ranges of CuO NPs were approximately from 5 nm to 50 nm. This indicated that the synthesized CuO NPs were a narrow distribution of diameters and the average particle size approximately 50 nm was of achieved [21]. FTIR spectrum FTIR spectrum of the CuO NPs and pretreated CuO NPs -cotton fabric is given in figure (11).…”
Section: Tem Analysismentioning
confidence: 94%
“…Silver nanoparticles were prepared by chemical reduction method [9,10]. All solutions were prepared in deionized water.…”
Section: Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%